Accurate finite element modeling of pretensioned prestressed concrete beams. (15th October 2015) - Yapar, O.; Basu, P.K.; Nordendale, N.
Highlights: Nonlinear FEA of PSC beams using plastic-damage of concrete and slip-bond model. Improved analysis scheme gives highly accurate behavioral predictions. Validation of simulation results with results of laboratory experiments. Deficiencies of analysis schemes in recent publications are critically explored. Abstract: This paper presents a nonlinear finite element model for pretensioned prestressed concrete beams. The study presented here is an important step because it is, perhaps, for the first time that a prestressed concrete beam has been successfully modeled by nonlinear finite element analysis, allowing for plasticity and damage behavior of concrete and slip-bond failure behavior for strands. The model faithfully follows the actual loading history realistically, allowing for the construction sequence including the process of transfer of strand force. Existing results of finite element analysis are not reliable in the critical regions. Even the very recent ones do not seem to have been successful. In this study, all material and bond models used are based on experimental data. The simulation results are validated with data from actual load testing. Apart from examining the behavior of the beam up to the limit state, the response of the damaged beam after local bonded composite patch repair is also considered. For this purpose, the prestressed concrete beam specimens are manufactured and tested in the laboratory before and after they have been repaired with bonded composite patches. Satisfactory agreement between finite element predictions and test results of the virgin beam is noted.